2011
DOI: 10.1007/s12665-011-1127-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the distribution of potentially toxic elements in surface soils around an industrialized area of northwestern Greece

Abstract: In order to investigate the factors influencing the distribution of 32 potentially toxic elements in the Ptolemais-Kozani basin, northwestern Greece, 38 soil samples were collected and analyzed. Concentrations of Al, and Zn were determined by ICP-AES and concentrations of As, Bi, Cd, Cs, Mo, Rb, Sb, Th, Tl, and U by ICP-MS. Bivariate analysis, principal component analysis, and geostatistical analysis were employed to investigate the factors influencing the distribution of the elements determined in the study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 43 publications
4
25
0
6
Order By: Relevance
“…The mobility of Cr in this medium is rather poor due to low solubility of its minerals. However, Cr contents in surface soil are affected by local geology and geomorphology (Petrotou et al 2012). The pH and oxidation state have the highest influence on Cr mobility in soils.…”
Section: Chromiummentioning
confidence: 99%
“…The mobility of Cr in this medium is rather poor due to low solubility of its minerals. However, Cr contents in surface soil are affected by local geology and geomorphology (Petrotou et al 2012). The pH and oxidation state have the highest influence on Cr mobility in soils.…”
Section: Chromiummentioning
confidence: 99%
“…The most abundant element in soil is Fe, followed by Ca, Mg, Na, K and P. The rather elevated concentrations of Fe and Mg, were expected, as in the study area ophiolitic (ultramafic) rocks, which contain the above mentioned elements in noteworthy amounts, are present (Skordas and Kelepertsis, 2005;Petrotou et al, 2010Petrotou et al, , 2012Skordas et al, 2010Skordas et al, , 2013. A study (Kelepertzis, 2014) regarding agrcultural soils in Argolida, Greece, has reported slightly different average concentrations for Fe, P and K (27100 mg kg -1 , 3000 mg kg -1 and 900 mg kg -1 , respectively).…”
Section: Resultsmentioning
confidence: 55%
“…One would expect that, since these trees grow on soil enriched in Fe its elevated concentrations would be directly associated with their geogenic origin. Possibly, because Fe is found in resistant minerals is not readily available (Megremi, 2010;Petrotou et al, 2010).…”
Section: Elemental Relationships Between the Sampled Meansmentioning
confidence: 99%
See 1 more Smart Citation
“…During lignite combustion the mineral matter of lignite undergoes a series of physical and chemical changes. Some minerals contained in the lignite ashes (fly ash, bottom ash, stack-gas ash), are initial constituents of the mined lignite, while some others are formed during the combustion of the lignite or by the soaking of the fly and bottom ashes with water during its transportation by conveyor belt from the Power Plants to the ash disposal areas (e.g., Filippidis et al, , 1996Kassoli-Fournaraki et al, 1992;Kolovos et al, 2002;Kantiranis et al, 2005;Petrotou et al, 2012;Tsirambides and Filippidis, 2012;Nikolaidou, 2014).…”
Section: Introductionmentioning
confidence: 99%